AUDIENCE RESPONSE OF RACISM IN HIDDEN FIGURES MOVIE - Suarnaningsih, Rina; Junaid, Syahruni; Nahdhiyah, Nahdhiyah (Elite : English and Literature Journal, 2020)
This study is about the audience response of racism toward Hidden Figures movie which is aimed to reveal the response of the audience about racism toward Hidden Figures Movie. This study used the reader-response theory by Louise Thursone. Data were analyzed by using interpretative qualitative method. The interview sheet is used as the instrument to find out the valid data. The study showed varied responses toward the racism of the Hidden Figures movie. The response of the audience is classified into two categories; positive and negative response